Jawabanmu

2014-05-27T17:51:28+07:00
 \sqrt{4 x^{2}-8x-5 }  -  \sqrt{4 x^{2} -20x+25} dikali  \frac{ \sqrt{4 x^{2}-8x-5 }  +  \sqrt{4 x^{2} -20x+25} }{ \sqrt{4 x^{2}-8x-5 }  +  \sqrt{4 x^{2} -20x+25} } 
=  \frac{ (4 x^{2}-8x-5) - (4 x^{2}-20x+25) }{ \sqrt{4 x^{2}-8x-5 }  +  \sqrt{4 x^{2} -20x+25} } 
=  \frac{ 4 x^{2}  - 8x - 5 - 4 x^{2}  + 20x -25 }{ \sqrt{4 x^{2}-8x-5 }  +  \sqrt{4 x^{2} -20x+25} } 
=  \frac{ 12x - 30 }{ \sqrt{4 x^{2}-8x-5 }  +  \sqrt{4 x^{2} -20x+25} } 
=   \frac{ \frac{12x}{x}  -  \frac{30}{x}  }{ \sqrt{ \frac{4 x^{2}}{x^{2}} - \frac{8x}{x^{2}} - \frac{5}{x^{2}}  }  +  \sqrt{ \frac{4 x^{2}}{x^{2}}  -  \frac{20x}{x^{2}} + \frac{25}{x^{2}} } } 
= 12 - 0 per akar 4 ditambah akar 4
= 12 per 2+2
= 12 per 4 
= 3